2021
DOI: 10.1111/cobi.13739
|View full text |Cite
|
Sign up to set email alerts
|

The scope and severity of white‐nose syndrome on hibernating bats in North America

Abstract: Article impact statement: Data sharing and coordinated monitoring are needed to assess species' response to threats to inform conservation planning at relevant scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
146
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 157 publications
(150 citation statements)
references
References 30 publications
3
146
1
Order By: Relevance
“…Our data show that E. fuscus has the most acidic skin ( Fig. 3 ), and this species is also more tolerant of WNS than the other bat species we measured ( Cheng et al , 2021 ). Although P. destructans can grow in vitro from 4.5–11 pH ( Raudabaugh and Miller, 2013 ; Vanderwolf et al , 2021 ), a carboxypeptidase enzyme produced by P. destructans was most active at 3–5 pH compared to 6.5–8.5 pH in vitro ( Beekman et al , 2018 ).…”
Section: Discussionsupporting
confidence: 48%
“…Our data show that E. fuscus has the most acidic skin ( Fig. 3 ), and this species is also more tolerant of WNS than the other bat species we measured ( Cheng et al , 2021 ). Although P. destructans can grow in vitro from 4.5–11 pH ( Raudabaugh and Miller, 2013 ; Vanderwolf et al , 2021 ), a carboxypeptidase enzyme produced by P. destructans was most active at 3–5 pH compared to 6.5–8.5 pH in vitro ( Beekman et al , 2018 ).…”
Section: Discussionsupporting
confidence: 48%
“…White-nose Syndrome (WNS) is an infectious disease of hibernating bats caused by a fungal pathogen ( Pseudogymnoascus destructans ; Pd ) 6 9 that was first detected in eastern North America in 2006 10 and has caused rapid and extreme population declines of several species of hibernating bats 11 14 . Over the past 15 years, extensive research has revealed much about the disease ecology of WNS, including the interactions between the pathogen, environments where bats hibernate, and the physiology of hibernating bats (see 12 for recent comprehensive review).…”
Section: Introductionmentioning
confidence: 99%
“…One of the challenging aspects of managing WNS is that the pathogen persists in the environment where bats hibernate, exposing bats to infection at the start of each hibernation season 19 , 20 . Understanding the specific conditions that affect disease severity and population declines where the pathogen invades and establishes 12 , 19 , 21 , 22 remains important for informing management response 4 , 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations